The Status and Progress of Women in the Middle East and North Africa - World Bank (World Bank, Washington, DC, 2017)
Over the years, the Middle East and North Africa (MENA) social and economic development group has regularly compiled briefs on the status and progress of women in the region for internal and external use. This is the third compendium and its content is drawn from existing data banks, records, statistics, and sources found in the public domain. The compendium includes a regional gender overview, country gender profiles covering all MENA countries, individual country gender briefs for Djibouti, the Arab Republic of Egypt, the Islamic Republic of Iran, Iraq, Jordan, Lebanon, Morocco, Saudi Arabia, Syrian Arab Republic, West Bank and Gaza, and the Republic of Yemen. In addition, the compendium provides information on research carried out in the area of gender and transport as there is an increased interest in the role of infrastructure in women’s economic empowerment, as well as research on attitudes regarding gender roles based on the world values survey.